Designing and Explaining the Competence Model of Knowledge Engineers in Municipalities (Study Case: Tehran Municipality) - Amin Seyyed Nosrati; Zahra Foroutani; Atyieh Bohrani (مدیریت دولتی)
Objective In today's fast-paced organizational environment, effectively managing knowledge is critical to ensure that valuable insights and expertise are not lost when employees leave. The role of a knowledge engineer is pivotal in capturing and codifying the tacit knowledge held by employees, making it accessible and preserving it within the organization. Despite its importance, there is a significant gap in the literature concerning the competence model for knowledge engineers. Therefore, this research was undertaken with the objective of identifying and calculating the essential competencies of knowledge engineers and designing a comprehensive model to guide their role within organizations. Methods This study is a qualitative, applied research project. The data were analyzed using thematic analysis, and the competencies of knowledge engineers were ranked using Friedman's test. The thematic analysis conducted in this research follows a thematic format approach, where interviews are the primary tool for extracting both main and secondary themes. In the initial stage, interview sessions were conducted with a group of experts and knowledge engineers from the Tehran Municipality. The primary competencies and components of knowledge engineers were identified based on these interviews, leading to the development and explanation of a competence model specifically for knowledge engineers within the Tehran Municipality. The validity of this model was then assessed through a survey of experts and knowledge managers, and the competencies were subsequently prioritized. The statistical sample in the first stage comprised 17 knowledge engineers from the Tehran Municipality, while in the second stage, involving the validation and ranking of competencies, the sample included 10 experts and knowledge managers. These participants were selected using the snowball sampling method. Data collection in the first stage was conducted through semi-structured interviews, while in the second stage, a questionnaire was employed to validate the model. The reliability of the interviews was determined using the test-retest method. Results The analysis of the interview themes yielded 113 open codes and 24 sub-themes, which were categorized into four main themes: managerial competencies, interpersonal and personality competencies, interpersonal and communication competencies, and technical and specialized competencies. The managerial competencies included indicators such as time management, managerial knowledge, organizational responsibility (management position), meeting management, and motivation. Interpersonal and personality competencies were defined by perceptive abilities, trustworthiness, charisma, flexibility, enthusiasm, extroversion, a jihadist spirit, work discipline, and strong memory. Interpersonal and communication competencies encompassed communication skills, impartiality, negotiation skills, trust-building, effective listening, teamwork, and social intelligence. Lastly, technical and specialized competencies included work expertise, documentation skills, and technical knowledge management. The results of the Friedman test revealed that, from the perspective of knowledge managers, interpersonal and communication competencies were deemed most important, followed by interpersonal and personality competencies, technical and specialized competencies, and managerial competencies. Conclusion The findings of this research provide a valuable foundation for municipal managers involved in knowledge management, particularly when selecting and developing knowledge engineers. The results are expected to enhance the quality of knowledge management processes by ensuring the effective utilization of human resources. Moreover, the competencies identified in this study can inform the development of training programs and development initiatives in the field of knowledge management within municipalities, thereby increasing the effectiveness and impact of these programs.